THE STUDY OF MODAL VERBS FROM A PEDAGOGICAL PERSPECTIVE: AN ANALYSIS OF TEXTBOOKS AND GRAMMARS - María Jesús Sánchez; Pilar Alonso; Ramiro Durán (Revista de Lingüística y Lenguas Aplicadas)
This paper shows how the indiscriminate combination of the form-function criterion in the traditional presentation of modal verbs brings more confusion than light to the subject due mostly to the fact that the grammatical simplicity of modal verbs clashes with their semantic complexity. In order to verify the treatment of modals in the EFL classroom, both a reduced but representative sample of textbooks and English grammar books will be analysed. Based on the findings of research conducted in this field, this article concludes that when studying modals in the EFL classroom the pragmatic uses of modal verbs should be primed over potential polysemic often indeterminate semantic values and/or grammatical criteria based on a higher or lower rank of graded modality.